PENGARUH HARGA, PERSONAL SELLING, KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN MOTOR PADA DEALER PT. YAMAHA PUTERA LANGKAPURA - Umar Bakti; Hairudin; Robi Setiawan (Jurnal Cakrawala Ilmiah, 2021)
This study aims to determine the effect of price, personal selling, product quality, and worth of mouth on purchasing decisions at PT Yamaha Putera Langkapura motorcycle dealership. The sampling technique used in this study was purposive sampling technique. The research subjects used were consumers who bought products at the PT Yamaha Putera Langkapura dealer in 2019 divided by the number of quarters totaling 89 respondents. The analytical tool used in this study is multiple linear regression. To get the test results in this study, a classic assumption test was carried out, namely the normality test, heteroscedasticity test, and multicorrelation test. Then the hypothesis testing is carried out. In this study the results of the Determination (R2) test showed that the purchase decision could be explained by price, personal selling, product quality and word of mouth by 58.5%. While the remaining 41.5% is influenced by other factors not included in this study. Simultaneously, the variable price (X1), personal selling (X2), product quality (X3) and word of mouth (X4) have a significant and positive effect on purchasing decisions at Dealer Yamaha Putera Langkapura.